The Effectiveness of Research-Led Teaching in Higher Education: Perceptions from Malaysia - Kothari, Mishal (2012)
Research-led teaching has become a fundamental issue within the academic world in recent years. In Malaysia, this topic has been under-researched since the general perception is that research does not play an active role in teaching. This research aims to find out Malaysian students’ perspective of research-led teaching with regards to the effectiveness of the teaching they experience. Based on the literature review that was available, a framework was developed and this research paper used a quantitative method by surveying 136 respondents. The data was analyzed using the Statistical Package for Social Science (SPSS) and also the structural equation modeling (SEM) Partial Least Square technique. The results showed that perceived benefits of research, perceptions of students’ about their lecturers’ research involvement and their research teaching experience has an effect on the effectiveness of teaching that they experience. In the context of this study, the results seem to be different between the two universities under examination with students’ from University A showing a clear link that research-led teaching affects teaching effectiveness as opposed to University B.